Evaluating clinical outcomes of routinely delivered task-shared care for depression in rural Haiti. (31st May 2021) - Rose, Alexandra L.; McBain, Ryan; Wilson, Jesse; Coleman, Sarah F.; Mathieu, Emmanuel; Fils-Aimé, J. Reginald; Affricot, Emmeline; Thérosmé, Tatiana; Dubuisson, Wilder; Eustache, Eddy; Smith, Stephanie L.; Raviola, Giuseppe
Abstract: Background: There is a growing literature in support of the effectiveness of task-shared mental health interventions in resource-limited settings globally. However, despite evidence that effect sizes are greater in research studies than actual care, the literature is sparse on the impact of such interventions as delivered in routine care. In this paper, we examine the clinical outcomes of routine depression care in a task-shared mental health system established in rural Haiti by the international health care organization Partners In Health, in collaboration with the Haitian Ministry of Health, following the 2010 earthquake. Methods: For patients seeking depression care betw|een January 2016 and December 2019, we conducted mixed-effects longitudinal regression to quantify the effect of depression visit dose on symptoms, incorporating interaction effects to examine the relationship between baseline severity and dose. Results: 306 patients attended 2052 visits. Each visit was associated with an average reduction of 1.11 in depression score (range 0–39), controlling for sex, age, and days in treatment (95% CI −1.478 to −0.91; p < 0.001). Patients with more severe symptoms experienced greater improvement as a function of visits ( p = 0.04). Psychotherapy was provided less frequently and medication more often than expected for patients with moderate symptoms. Conclusions: Our findings support the potential positive impact of scaling up routine mental health services in low- and middle-income countries, despite greater than expected variability in service provision, as well as the importance of understanding potential barriers and facilitators to care as they occur in resource-limited settings.